2005
DOI: 10.2188/jea.15.113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking and Age on Chronic Obstructive Pulmonary Disease in Japan

Abstract: BACKGROUND: The Global Initiative for Chronic Obstructive Lung Disease guidelines recommended a forced expiratory volume at one second per forced vital capacity as a standard diagnostic criterion of chronic obstructive pulmonary disease (COPD). A few reports on the risk factors of COPD have used the standard diagnostic criteria. In our study, the effects of age and smoking on COPD in Japan under the standard diagnosis criteria were evaluated. METHODS: Subjects were 11,460 participants aged 25-74 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
2
9
1
1
Order By: Relevance
“…1, we found that age, sex and smoking are substantial environmental risk factors of COPD phenotype and COPD-related quantitative trait (FEV1). This result agrees with the analysis performed by Kojima et al (2005), in which they showed age and smoking were strong risk factors for COPD under the standard diagnostic criteria. By analyzing the genetic risk factors of COPD phenotype, it appeared that two deleterious nsSNPs (rs1138272 and rs6712954) in BN1 (Fig.…”
Section: Construction Of Bayesian Networksupporting
confidence: 92%
“…1, we found that age, sex and smoking are substantial environmental risk factors of COPD phenotype and COPD-related quantitative trait (FEV1). This result agrees with the analysis performed by Kojima et al (2005), in which they showed age and smoking were strong risk factors for COPD under the standard diagnostic criteria. By analyzing the genetic risk factors of COPD phenotype, it appeared that two deleterious nsSNPs (rs1138272 and rs6712954) in BN1 (Fig.…”
Section: Construction Of Bayesian Networksupporting
confidence: 92%
“…occupational exposure, respiratory disease during childhood, undernourished status and poor healthcare). Strong associations between COPD and age among nonsmokers could be attributed not only to the accumulative effects of risk factors over time, but also to the age-related weakening of respiratory muscles that leads to decreased peak expiratory flow and FEV1/FVC by standardised spirometry tests [36]. In the current study, male nonsmokers were more likely to have COPD than female nonsmokers, probably a result of higher exposure to risk factors.…”
Section: Copd In Chinese Nonsmokers Y Zhou Et Almentioning
confidence: 47%
“…Young [69]2009MaleSpirometryNew Zealand654>40S. Kojima [70]2005Male and FemaleSpirometryJapan1146025–74S. Liu [71]2007Male and FemaleSpirometryChina3286>40T.…”
Section: Resultsmentioning
confidence: 99%